Motor performance, functional status and quality of life in children with dyslexia - Çetin, Sebahat Yaprak; Kitiş, Ali; Şen Kösem, Figen (The European Research Journal, 2018)
Objectives: The purpose of this study was to assess motor performance, functional status and quality of life in children with dyslexia by the Diagnostic and Statistical Manual of Mental Disorders Turkish version (DSM-IV-TR), and compare the outcome with typically developing children.Methods: This study includes 28 dyslexic and 28 typically developing children at the age of 7 to 12 years. Motor abilities and proficiencies were evaluated with the short form of the second version of the Bruininks Oseretsky Test of Motor Proficiency (BOTMP 2-SF). The Functional Independence Measure for Children (WeeFIM) was used to measure functional status. Quality of life in the children evaluated with the Pediatric Quality of Life Inventory (PedsQL).Results: There was a significant difference found between the results of the two groups on motor abilities, functional status and quality of life (p < 0.05).Conclusions: We think that, according to the obtained results, it is important to assess in detail and plan rehabilitation programs such as education at daily living activities in order to increase the quality of life in dyslexic children who were diagnosed in terms of motor performance.